63‐2: Distinguished Paper: Large‐scale Luminance Enhancement Film with Quantum Rods Aligned in Polymeric Nanofibers for High Efficiency Wide Color Gamut LED Display. Issue 1 (May 2016) - Qin, Jing; Wen, Zuoliang; Li, Shang; Hao, Junjie; Chen, Wei; Dong, Di; Deng, Jian; Wang, Dan; Xu, Bing; Wu, Dan; Wang, Kai; Sun, Xiaowei
Abstract : We present a large‐scale transparent luminance enhancement film with quantum rods aligned in polymeric nanofibers by electrospinning for high efficiency wide color gamut LED display. 18.4% brightness enhancement is achieved for LED display using aligned QR film with 0.45 polarization over an area of 5 cm 2 .